Intravenous administration of normal saline may be misinterpreted as a change of end-expiratory lung volume when using electrical impedance tomography - Sobota, Vladimír; Müller, Martin; Roubík, Karel (Scientific reports, 2019)
Electrical impedance tomography (EIT) is a noninvasive imaging modality that allows real-time monitoring of regional lung ventilation. The aim of the study is to investigate whether fast saline infusion causes changes in lung impedance that could affect the interpretation of EIT data. Eleven pigs were anaesthetized and mechanically ventilated. A bolus of 500 mL of normal saline was administered rapidly. Two PEEP steps were performed to allow quantification of the effect of normal saline on lung impedance. The mean change of end-expiratory lung impedance (EELI) caused by the saline bolus was equivalent to a virtual decrease of end-expiratory lung volume (EELV) by 227 (188-250) mL and decremental PEEP step of 4.40 (3.95-4.59) cmH2O (median and interquartile range). In contrast to the changes of PEEP, the administration of normal saline did not cause any significant differences in measured EELV, regional distribution of lung ventilation determined by EIT or in extravascular lung water and intrathoracic blood volume. In conclusion, EELI can be affected by the changes of EELV as well as by the administration of normal saline. These two phenomena can be distinguished by analysis of regional distribution of lung ventilation.
Keywords: Tomography; Electric Impedance; elektrická impedance; solný roztok; Infusions, Intravenous; intravenózní infuze; dechový objem; Tidal Volume; tomografie; Swine; Artifacts; ženské pohlaví; zvířata; plíce; artefakty; prasata; Female; Lung; Saline Solution; Animals